Novel monopole antenna technique for determination of moisture content in hevea rubber latex. - Ali, Ali Hamad (2011)
In this thesis the determination of moisture content in hevea latex using novel monopole antenna technique is described. The measurement set-up includes a computer controlled Professional Network Analyzer (PNA) of model N5230A and monopole antenna. The antenna was connected to the PNA using a low-loss coaxial cable to measure magnitude of reflection coefficient from 2.2 GHz to 2.7 GHz. Measurement of complex relative permittivity of hevea latex was done by using coaxial line probes (HP 85070B) coupled with the PNA. The actual moisture content was found by using standard oven drying method. Data analysis has been carried out to establish optimal operating frequency based on the relationship between the magnitude of reflection coefficient and moisture content from 20% to 80% for all frequencies where minimum reflections took place and other selected frequencies. Functional relationships have been developed between magnitude of reflection coefficient, frequency shifts and moisture content. The magnitude of reflection coefficient was found to increase linearly as moisture content increasing from 2.2 GHz to 2.3 GHz. A linear relationship between frequency shifts (Δf) and moisture content from 2.2 GHz to 2.7 GHz was also obtained. The performance characteristic of monopole antenna as a hevea latex moisture sensor was given as well as comparison between measured and calculated values of impedance at 2.30 GHz, results was found decreasing with increasing moisture content. The results obtained in this aspect are in good agreement at low moisture content (i.e. < 40%). The relationship between the reflection coefficient magnitude and measurement data at low moisture content section was more linear with higher sensitivity compared to those at high moisture content sections. Furthermore, the mean linearity error at low moisture content section was large than at high moisture content sections. The probability distribution of error was normal and almost symmetric with value of skewness equal to zero. By comparing the results from other microwave methods with the results obtained from this study, this technique is very potential and successfully determined the amount of moisture content in hevea latex from 20% to 80% at a frequency of 2.3 GHz. This technique is non-destructive and the sensor is very cheap which cost only two dollars and since there is no chemical reagent needed there will be no daily expenditure. This method is accurate and rapid because it does not requires laborious sample preparation and the whole operation only takes few minutes. The antenna can be used to measure specified range of moisture content in hevea latex based on measured magnitude of reflection coefficient alone at 2.30 GHz within ±1.5595% of error.